THE INFLUENCE OF LEADERSHIP STYLE, AND GREEN MANAGEMENT ACCOUNTING ON THE SUSTAINABILITY PERFORMANCE OF CATHOLIC UNIVERSITIES IN INDONESIA - Andrew, Richard; Lusy, Lusy; Pranata, Yosef (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Sustainability performance is an issue that has become phenomenal lately in the era of Industrial Revolution 5.0. Not only companies are the object of special attention towards sustainability performance based on profit goals, but non-profit (nonprofit) based organizations also continue to strive to achieve sustainability performance. The Catholic University as one of the non-profitoriented organizations must continue to maintain its performance in order to achieve sustainability performance. The object of research in this study are all Catholic universities in Surabaya and Jakarta. The choice of place is because the two cities are the two largest cities in Indonesia and have the best Catholic universities in Indonesia. Sampling technique in this study using purposive sampling. This type of research is quantitative research with questionnaires through Google Form with a Likert scale of 1-5.The purpose of this study was to analyze and examine the influence of leadership style, and Green Management Accounting on sustainability performance. The specific purpose of this study is to see the role of Green management accounting on the sustainability performance of Catholic universities in Indonesia is maintained in the midst of rapid technological developments in the Industrial Revolution 5.0. The urgency of this research is if the Catholic University in Indonesia has a different level of understanding, Knowledge-Based Leadership Style, Green Management Accounting and Sustainability Performance, specific specifications in this research, more focus on the theme of green Management Accounting and sustainable Accounting Research in terms of the level of leadership style, Green Management Accounting.